2014
DOI: 10.1212/wnl.0000000000000445
|View full text |Cite
|
Sign up to set email alerts
|

Progranulin protein levels are differently regulated in plasma and CSF

Abstract: While some correlation exists between plasma and CSF PGRN, age, sex, and genetic factors differently affect PGRN levels. Therefore, caution should be taken when using plasma PGRN to predict PGRN changes in the brain. These findings further highlight that plasma PGRN levels may not accurately predict clinical features or response to future frontotemporal lobar degeneration therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
78
6
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(101 citation statements)
references
References 29 publications
(32 reference statements)
15
78
6
2
Order By: Relevance
“…The observation that CSF levels, but not serum levels, of progranulin were reduced in FTD confirms and extends earlier findings from our group [8] and others [24,38,39] which demonstrated that progranulin levels in the CNS are regulated differently from those in the body periphery, both in healthy elderly subjects [24] and in various neurodegenerative diseases [8,38,39]. This differential regulation is in line with the notion that most CSF progranulin is either brain-derived or actively transported from the vascular compartment into the CSF, as suggested by the high intrathecal fraction of CSF progranulin (80-90%) [38].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The observation that CSF levels, but not serum levels, of progranulin were reduced in FTD confirms and extends earlier findings from our group [8] and others [24,38,39] which demonstrated that progranulin levels in the CNS are regulated differently from those in the body periphery, both in healthy elderly subjects [24] and in various neurodegenerative diseases [8,38,39]. This differential regulation is in line with the notion that most CSF progranulin is either brain-derived or actively transported from the vascular compartment into the CSF, as suggested by the high intrathecal fraction of CSF progranulin (80-90%) [38].…”
Section: Discussionsupporting
confidence: 92%
“…Here, we investigated progranulin levels in the CSF of a carefully selected FTD cohort that was negative for mutations in GRN and other dementia genes, as demonstrated by WES. Our findings show that the CSF levels of progranulin are reduced, even in mutation-negative FTD, and that this reduction extends beyond the recognised modification of CSF progranulin levels by the SNP rs5848 [24]. This suggests that decreased central nervous progranulin levels not only contribute to FTD in the relatively rare cases of pathogenic GRN mutations [4,25], but could actually represent a more general mechanism in FTD neurodegeneration.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…The effects of age and gender on blood and CSF PGRN levels have been recently studied, results are slightly discrepant showing no or minor effects. Blood and CSF PGRN levels were correlating with each other in these studies to a minor extent [15,31]. Inter-individual differences in serum PGRN concentrations are strongly determined by the rs5848 polymorphism related to FTD risk [32,33], which could have influenced group estimates of PGRN concentrations in studies that did not check for this genetic predisposition.…”
Section: Discussionmentioning
confidence: 79%